If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -3) = 18 Reorder the terms: 5(-3 + x) = 18 (-3 * 5 + x * 5) = 18 (-15 + 5x) = 18 Solving -15 + 5x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 5x = 18 + 15 Combine like terms: -15 + 15 = 0 0 + 5x = 18 + 15 5x = 18 + 15 Combine like terms: 18 + 15 = 33 5x = 33 Divide each side by '5'. x = 6.6 Simplifying x = 6.6
| 4(2v+7)+v=35+8v | | 2p+1=p+7 | | -5(-7-5x)=-115 | | 6x+7=2x+6 | | 3x+2=6-5x | | 729x^2+8=0 | | -2x+4=5 | | 81x^2+144x+64=0 | | 5h+4=2h+8 | | 15x^2+28x+12=0 | | 7(3x+4)=42 | | x^2-36=21 | | -4x-8=-20 | | (-5x)-x+14x-3x=0 | | (8-v)(5v+4)=0 | | 5x-4=-x-4 | | 10b^3-5b^2-2b+1= | | 2g+8=10 | | x-2.9=1.1 | | 7x+5=-3x-15 | | 91=n^2-n | | (x^2)+30x+7000=0 | | 56=n^2-n | | 90=n^2-n | | -3x+18=x+26 | | K^2=28 | | 5+2[3(8-2)]=0 | | 2*-x=12 | | 2x+8=30-9x | | 8x^4-8x^2+1=0 | | 12x^4y+2xy^3-8x^4y-7xy^3=0 | | (v+20)(v-24)=0 |